Optimalisasi Manajemen Alat Pelindung Diri dan Pelayanan Farmasi Klinis selama Pandemi COVID-19: Narrative Review - Kartika Citra Dewi Permata Sari; Nadia Farhanah Syafhan; Imanuel Sianipar (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2022)
Personal protective equipment (PPE) usage in health services plays an essential role in ensuring healthcare workers’ (HCW) and patients’ safety, especially during COVID-19 pandemic. On the other hand, the diversity of PPE types in the market, limited hospital budget and supplies, required PPE must be rationally managed. Pharmacists as supply managers and clinical care providers must implement PPE management optimization strategies to ensure PPE’s availability and avoid negative impacts such as increasing health service’s costs or PPE waste. This article aims to provide evidence-based strategies for PPE management in hospitals based on managing supply stages and clinical pharmacy services. The article was prepared using narrative literature review method from Google Scholar, ScienceDirect, and SpringerLink databases. Articles with topics related to PPE management; alternative uses of PPE, selection, planning, distribution, reuse, and clinical pharmacy services during the COVID-19 pandemic were included in this study. Based on the search, 30 articles and 13 policy guidelines were obtained which were included in this literature review. Management strategies included identifying and cohort supply need based on transmission risk, selecting PPE’s type, forecasting with calculation tools, avoiding just-in-time procurement, centrally distributed, and potential reuse. Clinical pharmacy services modification to minimize PPE use was also an optimizing strategy. For its implementation, pharmacists need to collaborate with other professionals in the hospital because it enhances success with a comprehensive approach. The recommended strategies are expected to assist the management of PPE in Indonesian hospitals, but its application must be tailored for each hospital.